2012
DOI: 10.1002/anie.201207304
|View full text |Cite
|
Sign up to set email alerts
|

CF Bond Activation of Unactivated Aliphatic Fluorides: Synthesis of Fluoromethyl‐3,5‐diaryl‐2‐oxazolidinones by Desymmetrization of 2‐Aryl‐1,3‐difluoropropan‐2‐ols

Abstract: How to lose fluorine: Biologically relevant oxazolidinones 1 were synthesized through the desymmetrization of unactivated aliphatic difluorides by Si‐induced catalytic CF bond‐cleavage using BSA/CsF (BSA=bis(trimethylsilyl)acetamide). The direct transformation of 2 with isocyanates into 1 by cascade carbamoylation/cyclization, in which cyclization is induced by Na‐assisted CF bond activation, was also achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(28 citation statements)
references
References 65 publications
0
27
0
1
Order By: Relevance
“…To gain insights into the origin of diastereocontrol in our AMR of phthalides, we considered a plausible mechanism. It has been previously demonstrated that BSA could be desilylated by catalytic amounts of Lewis base salts to afford amide salts that can be used to deprotonate carbon acids to promote their reactions with electrophiles . In a closely related transformation, catalytic amounts of alkali metal aryloxides and stoichiometric amounts of BSA in the presence of phase‐transfer catalysts have been used to promote the vinylogous aldol addition of γ‐butenolides.…”
Section: Resultsmentioning
confidence: 99%
“…To gain insights into the origin of diastereocontrol in our AMR of phthalides, we considered a plausible mechanism. It has been previously demonstrated that BSA could be desilylated by catalytic amounts of Lewis base salts to afford amide salts that can be used to deprotonate carbon acids to promote their reactions with electrophiles . In a closely related transformation, catalytic amounts of alkali metal aryloxides and stoichiometric amounts of BSA in the presence of phase‐transfer catalysts have been used to promote the vinylogous aldol addition of γ‐butenolides.…”
Section: Resultsmentioning
confidence: 99%
“…A plausible reaction mechanism for the asymmetric allylic substitution reaction of MBH fluorides 1 mediated by Me 3 SiCF 3 is shown in Figure . This transformation starts with the activation of the strongest C−F bond of allyl fluoride 1 by the silicon atom of Me 3 SiCF 3 . An ion pair of cationic intermediate I and a CF 3 carbanion should be generated by an S N 2′ addition of the chiral tertiary amine catalyst at the terminal alkenyl position of 1 with the release of stable F−SiMe 3 .…”
Section: Methodsmentioning
confidence: 99%
“…[16] Therefore,m any efforts have been made to synthesize these useful heterocyclic compounds,f or example through the allylic CÀHo xidation reaction of N-Boc amines [17] and the formal [3+ +2] cycloaddition reaction, [18] among others. [19] Recently,t he cyclization of CO 2 with propargylic amines to obtain 2-oxazolidinones has attracted much attention. So far,avariety of effective catalytic systems,s uch as silver /1,8-diazabicyclo-[5.4.0]undec-7-ene (DBU) [20] and NHC-gold complexes (NHC = N-heterocyclic carbene), [21] have been used to pro-mote this type of reaction.…”
mentioning
confidence: 99%